Outer stars : stories - Lunstrum, Kirsten Sundberg, 1979- (Katherine Anne Porter Prize in Short Fiction series, 2025)
"In these seven short stories, both realist and speculative, Sundberg Lunstrum considers life in the Anthropocene, an era marked by individual isolation, environmental degradation, and the erosion of our relationships with one another and our land. As they encounter heartbreak and new love, the aches and joys of parenthood, and the grief of bodies in decline, her characters seek connection, identity, and purpose. They ask the questions we all ask: Can we hold on to each other across the fractures that divide us? How do we find belonging in the face of great loss? And is it possible to locate meaning -- and even beauty -- in our darkest moments? The stories in Outer Stars present the tensions of our age with clarity, but they also leave the reader with hope, affirming the truth of human resilience and compassion."-- Provided by publisher.